Corrective Justice: An Economic Approach for Law - JANUARSYAH, Mas Putra Zenno; ASTAWA, I Gde Pantja; ATMASASMITA, Romli; GULTOM, Elisatris (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
Corruption has a negative impact on people’s lives and statehood. The strategic positions in State-owned enterprises (SOE) are vulnerable to abuse of power and authority which has an impact on state losses. The concept of interpretation of the legal system of state finance in SOE governance actually raises its own problems. The purpose of this study is to obtain an overview and analyze policy solutions for understanding law enforcement of state finance, state admission law, and SOE. Research methods is normative descriptive juridical on public companies and state finances laws. The inclusion of elements detrimental to state finances in the formulation of criminal acts of corruption brings certain legal consequences in the field of evidence law. The concrete facts in the court of law that there is no explicit difference in principle and consequently between public law and private law bring its own problems in the field of law. Efforts to support SOE in line with the principles of Good Corporate Governance (GCG) and efforts to save state finances are counterproductive. The results of the study as a framework for formulating policies to avoid the injustice of law enforcement in concreto towards the application elements of state financial losses.